Apophatic bodies : negative theology, incarnation, and relationality - Boesel, Chris; Keller, Catherine, 1953- (Transdisciplinary theological colloquia., 2010)
This work pursues the unlikely conjunction of apophasis and the body, not for the cachet of the 'cutting edge' but rather out of an ethical passion for the integrity of all creaturely bodies as they are caught up in various ideological mechanisms that threaten their dignity and material well-being.